2013
DOI: 10.1590/s1413-81232013001200029
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à compreensão da prescrição médica no Sistema Único de Saúde de um município do Sul do Brasil

Abstract: Fatores associados à compreensão da prescrição médica no Sistema Único de Saúde de um município do Sul do BrasilFactors associated with the understanding of medical prescriptions in the Unified Health System in a city in southern Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
17

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
0
11
0
17
Order By: Relevance
“…In our study, we found that the higher the patients' age, the higher their knowledge about dosage and usage time of the prescribed medication. This may be related to the fact that older people usually make use of continuous medications, which might be associated with greater knowledge (13) . A distinct result was found in another study, carried out with Unified Health System users in the municipality of Tubarão, Santa Catarina, Brazil, in which younger people understood the medication prescription better, when compared with older people (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we found that the higher the patients' age, the higher their knowledge about dosage and usage time of the prescribed medication. This may be related to the fact that older people usually make use of continuous medications, which might be associated with greater knowledge (13) . A distinct result was found in another study, carried out with Unified Health System users in the municipality of Tubarão, Santa Catarina, Brazil, in which younger people understood the medication prescription better, when compared with older people (13) .…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge might be related to the patient's comprehension concerning the offered orientations. The low educational level can be an obstacle to the information understanding (13) . The educational level directly interferes in the development of sanitary awareness, in the ability to understand the prescribed treatment, and in the self-care practice (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Quanto ao número de medicamentos prescritos, o valor médio encontrado foi superior ao encontrado por estudos anteriores [4,5]. Este resultado pode sugerir polifarmacoterapia nesta amostra, podendo ser justificada pela frequência de idosos (em torno de um quinto) na amostra em estudo, uma vez que o uso de vários medicamentos é uma característica dessa faixa etária [13].…”
Section: Discussionunclassified
“…Este resultado pode sugerir polifarmacoterapia nesta amostra, podendo ser justificada pela frequência de idosos (em torno de um quinto) na amostra em estudo, uma vez que o uso de vários medicamentos é uma característica dessa faixa etária [13]. Muitos medicamentos prescritos ao mesmo tempo podem interferir com o entendimento do paciente, pois estudos publicados sugerem que quando há menos medicamentos a serem administrados, também há menos informações a serem assimiladas, facilitando a compreensão dos usuários [4,8,14].…”
Section: Discussionunclassified
See 1 more Smart Citation